PENGARUH INTEGRATED MARKETING COMMUNICATIONS (IMC) DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK FURNITURE DI CV RACAK - Damayanti, Dila; Purwanto, Wahyu (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The purpose of this study is to determine the impact of Integrated Marketing Communication and product quality on the choice of buying furniture at CV Racak. The consequences of this review can be seen with the t test that the Integrated Marketing Communication variable has a non-significant influence on the purchasing decisions of CV Racak furniture. Evidenced by the value of tcount less thanttable (1.498 less than2.0345) and sig. 0.000 (0.000 less than0.05). The product quality variable influences the decision to purchase CV Racak furniture with tcount greather than ttable (7.060 greather than two.03693) and sig. 0.000 (0.000 less than0.05), whereas in the F test the Integrated Marketing Communication variables and product quality together influence the choice of buying CV Racak furniture with the follow-up effect of the F test Fcount greather than Ftable (89.095 greather than 3.29) and Sig. of 0.000 (0.000 less than0.05).